2008
DOI: 10.1016/j.neuro.2008.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Chronic exposure to glufosinate-ammonium induces spatial memory impairments, hippocampal MRI modifications and glutamine synthetase activation in mice

Abstract: Glufosinate-ammonium (GLA), the active compound of a worldwide-used herbicide, acts by inhibiting the plant glutamine synthetase (GS) leading to a lethal accumulation of ammonia. GS plays a pivotal role in the mammalian brain where it allows neurotransmitter glutamate recycling within astroglia. Clinical studies report that an acute GLA ingestion induces convulsions and memory impairment in humans. Toxicological studies performed at doses used for herbicidal activity showed that GLA is probably harmless at sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 50 publications
0
34
0
1
Order By: Relevance
“…Los animales se mantuvieron en condiciones ideales a una temperatura de 18-23 ºC, con humedad relativa del 40-70 %, con un régimen de alimentación y agua esterilizada y en ciclos de luz/oscuridad de 12 h. Los grupos de ratones (n=10) se asignaron aleatoriamente; los testigo (n=4) recibieron el vehículo (agua) y los tratados (n=6) recibieron el GLA (97 % de pureza; Sigma, Saint Louis, MO, USA) en dosis de exposición diarias de 5, 7.5 o 10 mg/kg de peso corporal/v.o./5-ó 15-días de tratamiento (dt). Las dosis de exposición fueron seleccionadas con base en lo establecido por Calas et al (2008), el tiempo de exposición de 5-dt es debido a que, en el ratón, los espermatozoides permanecen en el epidídimo entre 5 y 7 días, mientras que a los 15-d se da la remoción de histonas y el cambio de proteínas de transición por protaminas (Eddy y O'brien 1989, Boussouar et al 2014. Los animales fueron sacrificados por dislocación cervical 24 h después de la última administración.…”
Section: Materiales Y Métodosunclassified
“…Los animales se mantuvieron en condiciones ideales a una temperatura de 18-23 ºC, con humedad relativa del 40-70 %, con un régimen de alimentación y agua esterilizada y en ciclos de luz/oscuridad de 12 h. Los grupos de ratones (n=10) se asignaron aleatoriamente; los testigo (n=4) recibieron el vehículo (agua) y los tratados (n=6) recibieron el GLA (97 % de pureza; Sigma, Saint Louis, MO, USA) en dosis de exposición diarias de 5, 7.5 o 10 mg/kg de peso corporal/v.o./5-ó 15-días de tratamiento (dt). Las dosis de exposición fueron seleccionadas con base en lo establecido por Calas et al (2008), el tiempo de exposición de 5-dt es debido a que, en el ratón, los espermatozoides permanecen en el epidídimo entre 5 y 7 días, mientras que a los 15-d se da la remoción de histonas y el cambio de proteínas de transición por protaminas (Eddy y O'brien 1989, Boussouar et al 2014. Los animales fueron sacrificados por dislocación cervical 24 h después de la última administración.…”
Section: Materiales Y Métodosunclassified
“…GLF exposure triggers convulsions and memory impairment. GLF expsoure produces moderate to severe convulsions and memory loss Watanabe and Sano, 1998;Ohtake et al, 2001;Park et al, 2006Park et al, , 2013Mao et al, 2011a andb, 2012), as well as causes structural changes to several brain regions, including the cortex and hippocampus (Calas et al, 2008;Meme et al, 2009;Park et al, 2006 ), two brain structures rich in NMDARs that play an important role in learning and memory processes.…”
Section: Glufosinate (Glf)mentioning
confidence: 99%
“…It is suggested that these modifications may be causally linked one to another. Hippocampal MRI texture and spatial memory alterations might be the consequences of hippocampal glutamate homeostasis modification (Calas et al, 2008).…”
Section: Glufosinate (Glf)mentioning
confidence: 99%
See 1 more Smart Citation
“…By using MRI (magnetic resonance imaging) we have recently demonstrated that chronic administration of L-PPT causes structural dose-dependent changes in several brain structures, including the somatosensorial cortex, hippocampus and striatum (Calas et al 2008;Meme et al 2009a). However, the relationship between the reduction in GS activity and the mechanisms of this L-PPT neurotoxicity are unclear.…”
mentioning
confidence: 99%